Aqueous Leaf Extract of Jatropha mollissima (Pohl) Bail Decreases Local Effects Induced by Bothropic Venom. (26th October 2016) - Gomes, Jacyra Antunes dos Santos; Félix-Silva, Juliana; Morais Fernandes, Júlia; Geraldo Amaral, Juliano; Lopes, Norberto Peporine; Tabosa do Egito, Eryvaldo Sócrates; da Silva-Júnior, Arnóbio Antônio; Maria Zucolotto, Silvana; Fernandes-Pedrosa, Matheus de Freitas
Abstract : Snakebites are a serious worldwide public health problem. In Brazil, about 90% of accidents are attributed to snakes from the Bothrops genus. The specific treatment consists of antivenom serum therapy, which has some limitations such as inability to neutralize local effects, difficult access in some regions, risk of immunological reactions, and high cost. Thus, the search for alternative therapies to treat snakebites is relevant. Jatropha mollissima (Euphorbiaceae) is a medicinal plant popularly used in folk medicine as an antiophidic remedy. Therefore, this study aims to evaluate the effect of the aqueous leaf extract from J. mollissima on local effects induced by Bothrops venoms. High Performance Liquid Chromatography with Diode Array Detection analysis and Mass Spectrometry analysis of aqueous leaf extract confirmed the presence of the flavonoids isoschaftoside, schaftoside, isoorientin, orientin, vitexin, and isovitexin. This extract, at 50–200 mg/kg doses administered by intraperitoneal route, showed significant inhibitory potential against local effects induced by Bothrops erythromelas and Bothrops jararaca snake venoms. Local skin hemorrhage, local edema, leukocyte migration, and myotoxicity were significantly inhibited by the extract. These results demonstrate that J. mollissima extract possesses inhibitory potential, especially against bothropic venoms, suggesting its potential as an adjuvant in treatment of snakebites.